Hospital‐ and community‐associated methicillin‐resistant Staphylococcus aureus: a 6‐year surveillance study of invasive infections in Chinese children. (10th September 2013) - Qiao, Yanhong; Dong, Fang; Song, Wenqi; Wang, Lijuan; Yang, Yonghong; Shen, Xuzhuang
Abstract Aim To investigate and compare the characteristics of invasive hospital‐associated (HA) and community‐associated (CA) methicillin‐resistant Staphylococcus aureus (MRSA) infections in Chinese children. Methods Clinical data on 59 paediatric patients with invasive MRSA isolated from the normally sterile sites between 2006 and 2011 were obtained from the clinical MRSA surveillance database of Beijing Children's Hospital. The molecular characteristics of the invasive MRSA strains were then analysed. Results Invasive MRSA infections rose from 0.89 per 10 000 admissions in 2006 to 3.75 in 2011, with a notable increase in invasive CA‐MRSA infections from 0 to 2.43 over the same period. The median age of the CA patients (n = 29) was 0.33 years, compared with 1.17 years for the HA patients (n = 30). Multisite infection, severe pneumonia and empyema were found in 55.2%, 73.1% and 61.5% of CA children and in 30%, 32% and 24% of HA patients, respectively. ST59‐MRSA‐IVa accounted for 40.7% of all isolates and the Panton–Valentine leukocidin (PVL) gene carriage rate was significantly higher in patients with necrotizing pneumonia and osteoarthritis than in those with other diseases. Conclusion The incidence of paediatric invasive MRSA infection, particularly CA‐MRSA infection, increased in Chinese children between 2006 and 2011. The invasive infections caused by CA‐MRSA occurred more frequently in younger children with more severe pneumonia or empyema.